2005
DOI: 10.1128/cdli.12.6.713-721.2005
|View full text |Cite
|
Sign up to set email alerts
|

Protective Antigen and Toxin Neutralization Antibody Patterns in Anthrax Vaccinees Undergoing Serial Plasmapheresis

Abstract: Recipients of licensed anthrax vaccine (AVA; Biothrax) could serve as a source of hyperimmune plasma and immunoglobulin for therapy and prophylaxis. We measured serum antibodies during serial weekly to biweekly plasmapheresis in 38 individuals previously vaccinated with 4 to 27 doses of AVA. Immunoglobulin G (IgG) to protective antigen (PA) and toxin neutralization assay (TNA) antibody levels were highly correlated (r ‫؍‬ 0.86930 and P < 0.0001 for anti-PA concentration versus TNA concentration). Significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
24
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 41 publications
5
24
1
Order By: Relevance
“…Binding of PA impedes toxin entry into cells, and is important in neutralizing B. anthracis LT in vivo and in vitro [20]. We and others have shown that there is strong correlation between IgG to PA and toxin-neutralizing activity after human infection with virulent anthrax, and vaccination with AVA [21,22].…”
Section: Discussionmentioning
confidence: 94%
“…Binding of PA impedes toxin entry into cells, and is important in neutralizing B. anthracis LT in vivo and in vitro [20]. We and others have shown that there is strong correlation between IgG to PA and toxin-neutralizing activity after human infection with virulent anthrax, and vaccination with AVA [21,22].…”
Section: Discussionmentioning
confidence: 94%
“…There is a good correlation between PA-specific Ab titers and toxin neutralization by sera from patients who have survived B. anthracis infection (29). Consequently, there is considerable interest in development of efficacious vaccines which incorporate PA as the immunogen but involve fewer immunizations, boost immunological memory, and prolong neutralizing Ab production while stimulating a minimal inflammatory response (28,29).…”
mentioning
confidence: 99%
“…The current AVA anthrax vaccine administered to U.S. military personnel consists of the Bacillus anthracis protective antigen (PA) and induces PA-specific antibody (Ab) titers sufficient to neutralize anthrax toxin (28,29). However, the anti-PA Ab titers are not sustained, and individuals require administration of multiple booster vaccines to maintain toxin-neutralizing Ab titers (http://www.anthrax.osd.mil/vaccine/schedule.asp#).…”
mentioning
confidence: 99%
“…These toxins are classic A-B toxins, where lethal factor and edema factor represent the active moieties and protective antigen (PA) represents the cell-binding moiety (5,6,20). Humoral immunity to PA can successfully mediate protection from lethal challenges in animal models of inhalation anthrax, and the protection is correlated with the ability of PA-specific antibodies to neutralize LeTx in vitro in the toxin neutralization assay (TNA) (17,21,22,35,36,41).While PA-specific antibody titer has been shown to correlate with TNA titers in vitro, this relationship demonstrates variability among different studies and in different species (19,37,40,43,48,50). Most PA-specific neutralizing monoclonal antibodies (MAbs) show a more invariable linear relationship between concentration and toxin neutralization (4, 46).…”
mentioning
confidence: 99%
“…While PA-specific antibody titer has been shown to correlate with TNA titers in vitro, this relationship demonstrates variability among different studies and in different species (19,37,40,43,48,50). Most PA-specific neutralizing monoclonal antibodies (MAbs) show a more invariable linear relationship between concentration and toxin neutralization (4, 46).…”
mentioning
confidence: 99%